3D modeling of source and reservoir rock characteristics in key oil and gas fields, Gippsland Basin, Southern Australia - Kamalia Norjannah Kamalrulzaman; Mohamed Ragab Shalaby; Md Aminul Islam (Results in Earth Sciences)
Despite extensive hydrocarbon production from the Gippsland Basin, limited integrated 3D modeling studies have comparatively assessed the structural, geochemical, and petrophysical variations between the Kingfish and Volador formations across oil- and gas-producing fields. This gap hampers accurate reservoir characterization and development strategies. To address this, a comparative 3D modeling analysis was conducted on the Kingfish and Volador formations in the Kingfish Oil and Kipper Gas fields, Gippsland Basin, Australia. Structural analysis revealed NW-SE trending steep faults (70–72°) in the Kingfish Field and shallower WNW-ESE faults (62.5–65°) in the Kipper Field. Facies models indicated similar stratigraphic successions, with upper high-energy sandstones transitioning to organic-rich shales at the base. Geochemical analysis showed the Kingfish Formation has TOC of 1.0–12.0 wt%, HI of 120–140 mg HC/g TOC, and higher maturity (Tmax 422–430 °C; % VR 0.50–0.52 %), consistent with deeper burial. In contrast, the Volador Formation has TOC of 2.0–6.0 wt%, higher HI (150–210 mg HC/g TOC), but lower maturity (Tmax 422.5–428 °C; % VR 0.48–0.49 %). Petrophysical results showed superior reservoir quality in the Volador Formation, with porosity of 10–25 %, permeability up to 10 mD, low clay volume (0–25 %), and water saturation of 50–100 %. The Kingfish Formation displayed more variable porosity (2.5–22.5 %), lower permeability (<10 mD), higher clay content (2.5–55 %), and water saturation of 40–95 %. Limited data from deeper Kingfish sections highlight the need for further exploration